Variation in echolocation call frequencies in two species of free-tailed bats according to temperature and humidity - Chaverri Echandi, Gloriana (2017)
Bats can actively adjust their echolocation signals to specific habitats and tasks, yet it is not known if bats also modify their calls to decrease atmospheric attenuation. Here the authors test the hypothesis that individuals emit echolocation calls ideally suited to current conditions of temperature and humidity. The authors recorded two species, Molossus molossus and Molossops temminckii, in the field under different conditions of humidity and temperature. For each species, two calls were analyzed: the shorter frequency modulated (FM) signals that bats emitted as they approached the recording microphone, and the longer constant frequency (CF) calls emitted thereafter. For each signal, the authors extracted peak frequency and duration, and compared these parameters among species, call type, and environmental conditions. The authors' results show significant differences in peak frequency and duration among environmental conditions for both call types. Bats decreased the frequency and increased duration of CF calls as atmospheric attenuation increased; using a lower-frequency call may increase the range of detection by a few meters as atmospheric attenuation increases. The same trend was not observed for FM calls, which may be explained by the primary role of these signals in short-range target localization.